The dependence of confinement on the isotope mass in the core and the edge of AUG and JET-ILW H-mode plasmas. (22nd December 2021) - Schneider, P.A.; Angioni, C.; Frassinetti, L.; Horvath, L.; Maslov, M.; Auriemma, F.; Cavedon, M.; Challis, C.D.; Delabie, E.; Dunne, M.G.; Climent, J.M.Fontdecaba; Hobirk, J.; et al.
Abstract: Experiments in ASDEX Upgrade (AUG) and JET with the ITER-like wall (JET-ILW) are performed to separate the pedestal and core contributions to confinement in H-modes with different main ion masses. A strong isotope mass dependence in the pedestal is found which is enhanced at high gas puffing. This is because the ELM type changes when going from D to H for matched engineering parameters, which is likely due to differences in the inter ELM transport with isotope mass. The pedestal can be matched in H and D plasmas by varying only the triangularity and keeping the engineering parameters relevant for core transport the same. With matched pedestals Astra/TGLF (Sat1geo) core transport simulations predict the experimental profiles equally well for H and D. These core transport simulations show a negligible mass dependence and no gyro-Bohm scaling is observed. However, to match the experimental observations at medium β it is required to take the fast-ion dilution and rotation into account. This is not enough for high β plasmas where for the first time a profile match between H and D plasmas was achieved experimentally. Under these conditions quasilinear modelling with TGLF over predicts the transport in the core of H and D plasmas alike.